Unfolding the muon neutrino flux ... - Kardum, Leonora (TU Dortmund, 2023)
The IceCube Neutrino Observatory, situated at the South Pole within a cubic kilometer of underground ice, is a state-of-the-art experiment for detecting particles of high energies, with a special focus on investigating neutrino physics. The neutrino flux can be divided into three distinct components: astrophysical, originating from extraterrestrial sources; conventional, arising from the decay of pions and kaons in atmospheric cosmic ray cascades; and the prompt component, which has yet to be detected and stems from the decay of charmed hadrons. This study aims to reconstruct the total flux of neutrinos at Earth and places a particular emphasis on examining the predicted angular dependence. Unfolding encompasses a collection of techniques that aim to determine a quantity in a manner independent of specific assumptions, thereby removing the influence of various assumptions made during the process. In this analysis, the energy spectrum of muon neutrinos is unfolded with the employment of an innovative ... : Das IceCube Neutrino Observatory, das sich am Südpol in einem Kubikkilometer unterirdischen Eises befindet, ist ein hochmodernes Experiment zum Nachweis von Teilchen mit hoher Energie, wobei der Schwerpunkt auf der Untersuchung der Neutrinophysik liegt. Der Neutrinofluss kann in drei verschiedene Komponenten unterteilt werden: astrophysikalische Neutrinos aus extraterrestrischen Quellen; konventionelle Neutrinos, aus dem Zerfall von Pionen und Kaonen in atmosphärischen Luftschauern; und prompte Neutrinos, die noch nicht gemessen wurden, aber aus dem Zerfall von Hadronen aus Charm-Quarks erwartet werden. Diese Studie zielt darauf ab, den Gesamtfluss der Neutrinos auf der Erde zu rekonstruieren, und legt einen besonderen Schwerpunkt auf die Untersuchung der vorhergesagten Winkelabhängigkeit. Die Entfaltung umfasst eine Reihe von Techniken, die darauf abzielen, eine physikalische Größe modellunabhängig zu bestimmen. In dieser Analyse wird das Energiespektrum von Myon-Neutrinos mit Hilfe einer innovativen ...